Islamische Militärseelsorge in Deutschland zwischen Kriegs- und Friedensethik: Bestandsaufnahme und grundlegende Überlegungen zu einem neuen Forschungs- und Berufsfeld - Abdallah, Mahmoud (International journal of practical theology, 2025)
This article provides a fundamental reflection on Islamic military chaplaincy (IMS) in Germany. It explains who can provide this service, how it is structured, and the value it adds, while acknowledging that there are no easy answers. The argument centers on four key questions: 1) The juridical-legal basis of Islamic military chaplaincy; 2) The theological foundation of the new research and working field of IMS; 3) Peace ethics in Islam and its contribution to the German military; and 4) The challenges and future prospects of IMS. Through this multifaceted approach, the article highlights the potential of the emerging field of IMS in Germany.